Determinants Of Revisit Intention Situ Candi Cangkuang Garut: Social Exchange Theory Perspective - Mita Mustika; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of authenticity, historical culture, social value, and experiential quality on revisit intention through the role of visitor engagement mediation in tourists from Situ Candi Cangkuang, Garut based on the perspective of social exchange theory. This study uses a quantitative approach with a survey method involving 162 tourists who visited Situ Candi Cangkuang, Garut. Data analysis was carried out using structural equation modeling based on partial least squares with the help of smartpls software version 3.0. Based on the results of hypothesis testing, authenticity, historical culture, social value, and experiential quality are proven to have a positive effect on revisit intention through the mediation role of visitor engagement. The novelty of this research lies in the integration of social value and experiential quality as antecedent variables in the revisit intention model in cultural and historical heritage tourism destinations. Managerially, the findings of this study provide implications for the management of Situ Candi Cangkuang Garut to develop a strategy that focuses on improving the quality of tourist experiences, preserving the authenticity of destinations, strengthening historical and cultural values, and creating social values to strengthen visitor engagement and increase tourist revisit intention. Scientifically, this study expands the application of social exchange theory in the context of cultural tourism by integrating social value and experiential quality as antecedent variables that contribute to the formation of visitor engagement, thereby providing a more comprehensive understanding of the mechanism of forming revisit intention. It is further recommended to develop this research model by integrating other relevant variables in the perspective of social exchange theory so as to provide a more comprehensive understanding of the factors that influence revisit intention.